Titanium and Iron Oxide Nanoparticles for Cancer Therapy: Surface Chemistry and Biological Implications - Kawassaki, Rodrigo Ken; Romano, Mariana; Dietrich, Natasha; Araki, Koiti (Frontiers in Nanotechnology, 2021)
Cancer is currently one of the most challenging among all diseases due to its ability to continuously evolve into a more complex multidimensional system, in addition to its high capability to spread to other organs and tissues. In this context, the relevance of nanobiomaterials (NBMs) for development of new more effective and less harmful treatments is increasing. NBMs provide the possibility of combining several functionalities on a single system, expectedly in a synergic way, to better perform the treatment and cure. However, the control of properties such as colloidal stability, circulation time, pharmacokinetics and biodistribution, assuring the concentration in specific target tissues and organs, while keeping all desired properties, tend to be dependent on subtle changes in surface chemistry. Hence, the behavior of such materials in different media/environment is of uttermost relevance and concern, since it can compromise their efficiency and safety on application. Given the bright perspectives, many efforts have been focused on the development of nanomaterials fulfilling the requirements for real application. These include robust and reproducible preparation methods to avoid aggregation while preserving the interaction properties. The possible impact of nanomaterials in different forms of diagnosis and therapy have been demonstrated in the past few years, given the perspectives on how revolutionary they can be in medicine and health. Considering the high biocompatibility and suitability, this review is focused on titanium dioxide and iron oxide based nanoagents highlighting the current trends and main advancements on the research for cancer therapies. The effects of phenomena, such as aggregation and agglomeration, the formation of the corona layer, and how they can compromise relevant properties of nanomaterials and their potential applicability, are also adressed. In short, this review summarizes the current understanding and perspectives on such smart nanobiomaterials for diagnostic, treatment and theranostic of diseases.